Crystal-plastic deformation and chemical evolution of clinoamphibole - Cumbest, Randolph J. (Virginia Polytechnic Institute and State University, 1988)
Clinoamphibole from a mylonitic amphibolite, located on Senja, Norway, exhibits microstructures characteristic of dynamic recrystallization, including larger host grains in a finer grained matrix of needle shaped amphibole. The matrix amphibole defines an LS fabric and host grains have core and mantle structures with a core containing undulose to patchy extinction and (100) deformation twinning surrounded by a mantle of recrystallized grains. In addition intragranular grains also occur within the cores. TEM analysis of the host grains revealed high densities of dislocations, dislocation arrays/subgrain boundaries parallel to (hk0), stacking faults, and (100) deformation micro-twins. Dark field, weak beam images show that the dislocations are commonly dissociated. Diffraction contrast experiments compared with computer simulation of dislocation images indicate the primary unit Burgers vector is [001]. This information in conjunction with trace analysis of glide loops and dislocation line direction shows that the following glide systems were operative: [001]{110}, [001](100), and possibly [001](010), in order of relative occurrence. These data along with dislocation energies are considered in order to propose a possible model for the [001] unit Burgers vector in the clinoamphibole structure. TEM also showed that matrix grains and intragranular grains have relatively low defect densities, and that the intergranular new grains occur at localities in the host grains characterized by high densities of dislocations. These observations along with the chemical and orientation relationships between the recrystallized grains and their host indicate that the new grains may have formed by heterogeneous nucleation and that further growth probably occurred by both strain assisted and chemically induced grain boundary migration or liquid film migration. This recrystallization event is interpreted to be synkinematic based on the fact that no recrystallization textures are present in the matrix grains and that the matrix grains ...